ANALYSIS OF COMPETITIVENESS AND EXPORT TRENDS OF INDONESIAN COCOA TO THE FIVE DESTINATION COUNTRIES FOR 2010-2019 - Nabilla Pratya Augustin; Edy Prasetyo; Siswanto Imam Santoso (Socio-Economics/Agribusiness Department, 2021)
This study aims to analyze the competitiveness of Indonesian cocoa exports to five destination countries, namely China, Germany, Malaysia, Singapore, and USA and to analyze the trend of Indonesian cocoa exports for the forecasting of the next 5 years. The data source used is secondary data in the form of export value and volume from 2010-2019 which is sourced from uncomtrade. Data analysis methods used are RCA, EPD, and linear trend analysis. The results showed that the comparative analysis of the RCA method for the commodities of Indonesian cocoa beans, cocoa butter, cocoa paste, cocoa powder in 2010-2019 has an RCA > 1 which means that it is competitive and has a comparative advantage in destination countries. Based on a competitive analysis using the EPD method, the commodity of Indonesian cocoa beans, cocoa butter, cocoa paste, and cocoa powder in 2010-2019 have EPD retreat and falling star values. Based on linear trend analysis, the export value of Indonesian cocoa beans in 2020-2024 is predicted to continue to decline, cocoa butter and cocoa powder in 2020-2024 is predicted to continue to increase, and cocoa paste in 2020-2024 is predicted to increase and later decrease.